Prevalence trends, population characteristics and treatment outcomes of tuberculosis combined with diabetes in Southwest China: a register-based retrospective study - Kong, Deliang; Xia, Yongping; Wang, Xiangliu; Zhang, Yingtong; Zhong, Jiyuan; Zhang, Ting; Wu, Chengguo; Fan, Jun; Pu, Chuan (Frontiers in Public Health, 2024)
BackgroundThe global situation regarding the prevention and control of pulmonary tuberculosis (PTB) remains challenging. With the ongoing aging population and the increasing prevalence of chronic diseases, the epidemic of comorbid pulmonary tuberculosis and diabetes mellitus (PTB-DM) presents challenges to PTB control. We conducted this study given that current research on PTB-DM has primarily focused on clinical medicine and immunology, with limited reports on the true prevalence of population-wide PTB-DM in specific regions, as well as the heightened risk of PTB-DM co-prevalence due to aging and the high prevalence of DM in Chongqing, Southwest China.MethodsThis retrospective study used PTB case data from the PTB Information Management System within the China Information System for Disease Control and Prevention (CISDP). The medical records of 112,592 PTB patients registered in Chongqing from 2016 to 2022 were extracted. After excluding patients with incomplete records, those not residing in Chongqing, and individuals still undergoing treatment, a total of 108,003 PTB patients were included in the study. The trend in PTB-DM incidence was analyzed using the Joinpoint regression model, and population and clinical characteristics of patients were described using frequencies (n) and percentages. Chi-squared test and Fisher’s exact tests was used to compare groups, and multivariable logistic regression model with stepwise backward elimination based on the Wald test was used to examine risk factors for adverse treatment outcomes.ResultsFrom 2016 to 2022, the incidence rate of PTB in southwest China showed a decreasing trend (AAPC = -10.22, 95% CI: −11.49% −8.94%), while the incidence rate of PTB-DM increased rapidly (AAPC = 14.25, 95% CI: 11.35% 17.23%). The proportion of PTB-DM among PTB cases increased from 2.96 to 12.28%. PTB-DM patients were characterized by a higher proportion of males and older adult individuals, the age range of the patients was 11 100 years, with a mean age of 58.21 ± 12.02 years, with multiple positive aetiological results, and lower rates of proactive medical consultation. Among PTB-DM patients, successful outcomes accounted for 80.85%, while unsuccessful outcomes accounted for 19.15%. Although the number of PTB-DM patients with successful treatment outcomes increased overall (AAPC = 12.22, 95% CI: 10.30% 14.16%), the failure rate showed a gradual upward trend (AAPC = 14.18, 95% CI: 6.53% 27.67%). Older age, retreatment, referral, and multiple positive aetiological results were risk factors for adverse treatment outcomes among PTB-DM patients.ConclusionThe study presents the true prevalence of PTB-DM comorbidity in the general population of Southwest China, revealing a significant upward trend in its prevalence and a higher risk of adverse outcomes among PTB-DM patients. Future efforts should focus on the prevention and control of PTB-DM comorbidity, with early screening and standardized treatment for high-risk groups such as the older adult, as well as implementing comprehensive and effective treatment and management measures for patients.